Hubungan antara sleep hygiene dengan gangguan tidur pada anak sekolah dasar - Zakaria, Amin; Rismawati, Novi; Patria, Dion Kunto Adi; Jamil, Mokhtar; Nurmayuniya, Heny (Holistik Jurnal Kesehatan, 2026)
Background: Sleep disorders in elementary school-aged children are a problem that can affect growth and development, cognitive function, and academic achievement. Sleep hygiene, as the practice of good sleep habits, is an important factor in preventing sleep disorders. Despite the high prevalence of sleep disorders in children, research on the relationship between sleep hygiene and sleep disorders in the Kepanjen area, Malang Regency, is still limited. Purpose: To analyze the relationship between sleep hygiene and sleep disorders in elementary school-aged children. Method: This quantitative analytical study with a cross-sectional approach involved 4th, 5th, and 6th grade students at Kemiri 2 Public Elementary School, located in Kemiri Village, Kepanjen District, Malang Regency, East Java. The sample was selected using a total sampling technique, resulting in a sample of 68 respondents. Data collection used the Sleep Hygiene Index and Sleep Disturbance Scale for Children questionnaires, which have been tested for validity and reliability. Data analysis used the chi-square test with a p-value > 0.05. Results: The majority of respondents (72.1%) had good sleep hygiene. However, 55.9% of respondents required sleep monitoring, and 20.6% experienced sleep disturbances. Statistical testing showed a p-value of 0.028, indicating a significant relationship between sleep hygiene and sleep disturbances in elementary school children. Conclusion: Sleep hygiene is significantly associated with sleep disturbances in elementary school children. Good sleep hygiene practices can be a preventative measure to reduce the risk of sleep disturbances in school-aged children.   Keywords: Elementary School Children; Sleep Disturbances; Sleep Hygiene.   Pendahuluan: Gangguan tidur pada anak usia sekolah dasar merupakan permasalahan yang dapat memengaruhi tumbuh kembang, fungsi kognitif, dan prestasi akademik. Sleep hygiene sebagai praktik kebiasaan tidur yang baik, menjadi salah satu faktor penting dalam mencegah gangguan tidur. Meskipun prevalensi gangguan tidur pada anak cukup tinggi, penelitian mengenai hubungan sleep hygiene dengan gangguan tidur di wilayah Kepanjen, Kabupaten Malang masih terbatas. Tujuan: Untuk menganalisis hubungan antara sleep hygiene dengan gangguan tidur pada anak sekolah dasar. Metode: Penelitian kuantitatif analitik dengan pendekatan cross sectional melibatkan siswa kelas 4, 5, dan 6 di SDN 2 Kemiri yang berlokasi di Desa Kemiri, Kecamatan Kepanjen, Kabupaten Malang, Jawa Timur. Sampel dipilih menggunakan teknik total sampling, sehinggal didapatkan sampel sebanyak 68 responden. Pengumpulan data menggunakan kuesioner Sleep Hygiene Index dan Sleep Disturbance Scale for Children yang telah diuji validitas dan reliabilitasnya. Analisis data menggunakan uji chi square dengan p-value > 0.05. Hasil: Mayoritas responden memiliki sleep hygiene yang baik sebanyak 72.1%. Namun, 55.9% responden memerlukan pemantauan gangguan tidur dan 20.6% mengalami gangguan tidur. Uji statistik menunjukkan nilai p value 0.028 yang mengindikasikan adanya hubungan signifikan antara sleep hygiene dengan gangguan tidur pada anak sekolah dasar. Simpulan: Sleep hygiene memiliki hubungan yang signifikan dengan gangguan tidur pada anak sekolah dasar. Praktik sleep hygiene yang baik dapat menjadi upaya preventif dalam menurunkan risiko gangguan tidur pada anak usia sekolah.   Kata Kunci: Anak Sekolah Dasar; Gangguan Tidur; Sleep Hygiene.